2019
DOI: 10.17245/jdapm.2019.19.3.135
|View full text |Cite
|
Sign up to set email alerts
|

Making inferior alveolar nerve block more comfortable via computer-controlled local anesthetic delivery: A prospective clinical study

Abstract: Background The fear of needle insertion and pain during anesthesia is a source of patient dissatisfaction in dentistry. Inferior alveolar nerve block (IANB) remains the most common type of block and is in itself painful. Computer-controlled local anesthetic delivery (CCLAD) has been proven to reduce the pain associated with injection of anesthetics in various blocks. However, the efficacy of CCLAD for IANB in adults remains unknown. Methods Sixty-four adult patients req… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Studies from the late 1990s showed that patients' pain perception during administration of anesthesia was reduced by dentists’ better speed control in administering the anesthetic agent [ 4 , 5 ]. Likewise recent studies showed a preference for CCLAD over conventional syringe in terms of pain perception during administration and efficacy [ 6 , 7 ]. On the other hand, there are studies that show no significant difference in pain perception when comparing CCLAD with a conventional syringe [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies from the late 1990s showed that patients' pain perception during administration of anesthesia was reduced by dentists’ better speed control in administering the anesthetic agent [ 4 , 5 ]. Likewise recent studies showed a preference for CCLAD over conventional syringe in terms of pain perception during administration and efficacy [ 6 , 7 ]. On the other hand, there are studies that show no significant difference in pain perception when comparing CCLAD with a conventional syringe [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The heterogeneity was I2=91%, hence we applied the random effects model for analysis. (Figure 1) 18 This systematic review and meta-analysis aimed to assess the effect of alternative anesthesia techniques in reducing pain as compared to conventional technique in patients undergoing dental treatment or retreatment. With a stringent inclusion and exclusion criteria search was conducted with the 3 databases by the two reviewers and data was then extracted under recommended headings.…”
Section: ) Wh I C H S H Owe D T H a T T H E P A I N Wa S H I G H E R ...mentioning
confidence: 99%
“…As a result, varied techniques have been utilized to reduce patients' paininduced fear and anxiety, such as low-level laser therapy, superficial anesthesia, music therapy, psychosomatic methods, cold therapy of soft tissues, distracting techniques, employment of fine needles, computer-controlled local anesthetic delivery technique, and jet injection. However, all of these techniques have some restrictions and, therefore, they need to be superseded by more suitable approaches for pain reduction [2][3][4][5][6][7][8][9][10][11]. Inferior alveolar nerve block (IANB) has been widely used for the anesthesia of mandibular molar and premolar teeth during various dental procedures.…”
Section: Introductionmentioning
confidence: 99%